Analysis of the Effect of Wear on Tire Cornering Characteristics Based on Grounding Characteristics - Shupei Zhang; Yue Liu; Haichao Zhou; Wei Zhang; Yixiang Chen; Hongcheng Zhu (World Electric Vehicle Journal, 2023)
Electric vehicles can lead to accelerated tire wear, an inevitable phenomenon during tire usage that can affect the cornering characteristics determining handling stability. In order to simulate tire wear, a finite element model for tire wear was established using the UMESHMOTION subroutine and Arbitrary Lagrangian–Eulerian (ALE) adaptive meshing in ABAQUS, which is based on the Archard theory. The tire’s cornering characteristics were analyzed based on the obtained worn tire. The research results demonstrate that as the wear amount increases, the cornering stiffness and aligning stiffness of the tire also increase. When there are differences in wear on both tire shoulders with the same global wear, the change in cornering stiffness is not significant, while the aligning stiffness exhibits noticeable differences. To explain the above phenomenon, grounding characteristics were incorporated as mediator variables. The analysis results indicate that wear has an impact on the grounding characteristics. Additionally, statistically significant correlations exist between grounding parameters and cornering characteristics. In conclusion, wear affects the tire’s cornering characteristics by changing the grounding characteristics.